Self-sustainable housing on Mayreau (West Indies) - Cousin, René; Hiltrop, Stefan; Jestrovic, Sandra (JNRD - Journal of Natural Resources and Development, 2015)
This paper describes a conceptual approach for developing a local water and energy supply system for a resort on a small Caribbean island. The system designed is guided by four main criteria which are sustainability, lowest cost, least possible maintenance and design simplicity. According to this premise the selected concept includes an integrated solution for collecting and handling potable water and the supply of hot water and electricity for domestic use. The proposed techniques are not strictly specific to the island of Mayreau. They can also be adapted to comparable islands and regions.